Environmental health risk assessment of lead (Pb) exposure in well water near to a cement industry - Bendesa, Komang Yuda Putra; Daud, Anwar; Birawida, Agus Bintara; Amqam, Hasnawati; Palutturi, Sukri; Russeng, Syamsiar S.; Putro, Gurendro; Mohd Elias, Saliza (Sami Publishing Company, 2025)
The cement industry is one of the sources of heavy metal pollution that has the potential to negatively impact the environment, either through air, soil, or water. The objective of the current study is to determine the health risks of the population living near the cement industry and to develop measures to manage these risks. This is planned to be achieved by investigating the levels of concentration of Pb in well water, the rate of their entry, and the duration and frequency of exposure in the population. This study used a purposive sampling method, and the number of samples was calculated using the Slovin formula, which resulted in 20 well water sampling points and 40 human samples. This study analysed intake, risk quotient (RQ), and risk management. The novelty of this study lies in the fact that individuals residing near the cement industry face health risks not only from air exposure, but also from the consumption of well water. This is based on the calculation results, which show that heavy metal Pb in well water samples around the cement industry can pose a risk to the community both in real time and lifetime. The RQ value of Pb in adult respondents ranged from 0.224 to 1.349 and 0.289 to 1.734 for children. This study could influence the cement industry to focus more on waste disposal and manage their environmental effects on water. Regular checks and the use of exhaust emission filters, along with well covers, can significantly reduce the industry's environmental impact.